Uptake of HIV testing and counseling, risk perception and linkage to HIV care among Thai university students - Thana Khawcharoenporn; Krongtip Chunloy; Anucha Apisarnthanarak (BMC, 2016)
Abstract Background HIV testing and counseling (HTC) with linkage to care after known infection are key components for HIV transmission prevention. This study was conducted to assess HTC uptake, HIV risk perception and linkage to care among Thai university students. Methods An outreach HTC program was conducted in a large public university in Thailand from January 2013 to December 2014. The program consisted of brief HIV knowledge assessment, free HTC, HIV risk assessment and education provided by the healthcare personnel. Students were categorized into low, moderate and high-risk groups according to the pre-defined HIV risk characteristics. Results One-thousand-eight-hundred-one students participated in the program, 494 (27 %) underwent HTC. Independent characteristics associated with no HTC uptake included female sex (P < 0.001), lower HIV knowledge score (P < 0.001), younger age (P < 0.001) and students from non-health science faculties (P = 0.02). Among the 494 students undergoing HTC, 141 (29 %) were categorized into moderate or high-risk group, of whom 45/141 (32 %) had false perception of low HIV risk. Being heterosexual was independently associated with false perception of low HIV risk (P = 0.04). The rate of new HIV infection diagnosis was 4/494 (0.8 %). Of these 4 HIV-infected students, 3 (75 %) were men who have sex with men and only 2 of the 4 students (50 %) showed up for HIV continuity care. Conclusions An outreach HIV prevention program with HTC was feasible and beneficial in detecting HIV risk and infection among the university students. However, interventions to improve HTC uptake, HIV risk perception and linkage to care are needed.